Capacidade de retenção de cádmio do solo de fundo da estação de tratamento de esgoto de Passo Fundo-RS - Floss, Márcio Felipe (2008)
The representative addition of the population and consumption causes an increase in the volume of sewage generated, as well as the risks of soil contamination due to disposal of sewage in contact with the medium. Therefore it is necessary to know the behavior of the plume of contamination in the ground. In the case of contaminant migration study in the soil, when the target is far from the source of contaminant, the microorganisms become of secondary importance. The most harmful to the environment, in this case, are toxic metals present in the sewage. The high level of cadmium toxicity to animals, and the possibility of containing in the sewage, it was decided to study it. To obtain the parameters of contaminant mobility were conducted tests of batch and diffusion. The analyses of the batch test resulted in the distribution coefficient kd equal of 4.41 g/cm³, but through parametric analysis of the delay factor, the results showed that the interference factor that is not dominant in the system of migration, even by the time to contact contaminants in soil-testing of column be smaller than in the batch test. The analyses of the diffusion test showed a low diffusion of plume evolution of contamination. However, the analyses show that the migration of the contaminant in the ground moves slowly